Flow diversion for treatment of intracranial aneurysms: Mechanism and implications. Issue 6 (22nd April 2019) - Chua, Melissa M. J.; Silveira, Luke; Moore, Justin; Pereira, Vitor M.; Thomas, Ajith J.; Dmytriw, Adam A.
Abstract : Flow diverters are new generation stents that have recently garnered a large amount of interest for use in treatment of intracranial aneurysms. Flow diverters reduce blood flow into the aneurysm, with redirection along the path of the parent vessel. Flow stagnation into the aneurysm and neck coverage with subsequent endothelialization are the important synergistic mechanisms by which the therapy acts. Several studies have examined the mechanisms by which flow diverters subsequently lead to aneurysm occlusion. This review aims to provide a general overview of the flow diverters and their mechanism of action and potential implications. ANN NEUROL 2019;85:793–800.